analisis Analisis Manajemen Pelayanan Instalasi Gizi di Rumah Sakit Umum Daerah Arifin Achmad Provinsi Riau Tahun 2019: Analisis Manajemen Pelayanan Instalasi Gizi di Rumah Sakit Umum Daerah Arifin Achmad Provinsi Riau Tahun 2019 - Zela Familta; Elfindri Elfindri; Jasrida Yunita (Jurnal Kesehatan Komunitas, 2019)
Hospital nutrition services are very important and as a determinant of service quality. In Arifin Achmad Regional General Hospital, Riau Province, illustrates the lack of human resources so that many officers do double jobs and the lack of facilities and infrastructure such as water supply to the room. This study aims to analyze the Management of Class III Inpatient Nutrition Installation Services at Arifin Achmad Regional General Hospital, Riau Province. This study uses in-depth interviews, observations and questionnaires. Data management is done by qualitative and quantitative analysis techniques. This study uses data validity in the form of triangulation. Informants in this study were Nutrition Officers, Nutritionists, Head of Nutrition Installation, Head of Monitoring and Evaluation Sub-Sector and patients totaling 2 people. For quantitative research with a sample of 100 inpatients. The results showed that there were themes that emerged as the findings of this study. The themes are the lack of human resources and the lack of knowledge about each other's duties, the availability of facilities and infrastructure is still lacking such as damaged water heaters, less comfortable space and non-smooth water supply and the implementation of SOP that has not been optimal in the form of food serving. not on time, food delivery is not on time. There is a need to improve the management of Nutrition Installations at Arifin Achmad Regional General Hospital in Riau Province in accordance with established standards. Such as recruitment for human resources that are still lacking, completing damaged facilities and infrastructure such as water heaters, repairing supply of water that is still lacking, performing services according to SOPs such as delivering food to patients on time